A 2D layered cobalt-based metal–organic framework for photoreduction of CO2 to syngas with a controllable wide ratio range. Issue 2 (14th December 2022) - Wei, Mei-Juan; Xu, Xian-Yan; Song, Jia-Qi; Pan, Mei; Su, Cheng-Yong
Abstract : A two-dimensional cobalt-based metal–organic framework provides an available concept for the design of heterogeneous photocatalysts that can reduce CO2 to a controllable syngas using solar energy. Abstract : Photocatalytic CO2 reduction to syngas (a mixture of CO and H2 ) with adjustable composition is a prospective way to mitigate the energy shortage and the greenhouse effect. Herein, we synthesize a thermally stable two-dimensional cobalt-based metal–organic framework (denoted as "Co-TBAPy") consisting of cobalt metal centers and H4 TBAPy (1, 3, 6, 8-tetrakis( p -benzoic acid) pyrene) as an organic linker, which exhibits superior CO2 adsorption capability and a considerable specific surface area. In accordance with the energy levels of [Ru(bpy)3 ]Cl2 ·6H2 O as a sensitizer, Co-TBAPy is active for photocatalytic reduction of CO2 to syngas with a wide controllable ratio range between 0.14 and 1.65 under visible-light irradiation. Moreover, the proportion of CO : H2 = 1 : 2 and 1 : 3 favorable for the synthesis of methanol and methane, respectively, can be precisely regulated, which few MOF-based photocatalysts have achieved so far. Furthermore, combined with DFT calculation, we reveal the influence of the water content of the reaction system in the process of photocatalytic CO2 reduction to produce a controllable proportion of syngas, which is often a profound while elusive factor in photoreduction reactions. This work provides a feasible concept for the design and application of Co-MOF materials for the photoreduction of CO2 to syngas in practical industrial fields.